Resilience of Religious Culture and Supply Chain Practices in Traditional Islamic Communities in Industrial Era 4.0 in East Java - Ishomuddin Ishomuddin (International Journal of Supply Chain Management, 2020)
Abstract-Supply Chain 4.0 - the application of the Internet of Things, the use of advanced robotics, and the application of advanced analytics of big data in supply chain management: place sensors in everything, create networks everywhere, automate anything, and analyze everything to significantly improve performance and customer satisfaction. The Islamic community in East Java is dominated by traditional Islamic community groups. They are the basis of the Nahdlatul Ulama (NU) organization. This base spreads from all corners of the village to the cities. This study aimed to examine the relationship between resilience, supply chain practices, religion and industrial age 4.0 with mediating effect of culture. Traditional Islamic societies maintain activities that are commonly carried out in NU organizational activities, among others in the form of; manaqiban, diba'an, selametan, and tahlilan that have continued to be carried out since now even though the socio-cultural life of the community has changed. These activities are religious traditions that have survived until now. In fact, this activity has become a kind of habit carried out in government institutions, government and private institutions in the community. Based on the background above, it is interesting to conduct research related to Islamic culture and traditions carried out by a group of traditional Islamic societies in the industrial era 4.0 today. This study aims to understand the understanding of traditional Islamic societies in carrying out and maintaining Islamic traditions in today's modern life. This study uses the social definition paradigm, qualitative approach, and by using descriptive analysis in supply chain strategies. The data analysis strategy uses the method suggested by Miles, Huberman, and Saldana.